202 An Update on in Vitro and in Situ Experimental Techniques for Approximation of Ruminal Fiber Degradation. (21st September 2022) - Foster, Jamie L
Abstract: Measures of the quantity of chemical components are used to make certain assumptions about forage or feed quality. However, additional ruminal degradation kinetic measures are necessary for modern nutrient requirement models and more accurate estimates of intake and digestibility. The extent and rate of ruminal degradation is most easily and inexpensively measured with in vitro and in situ experimental techniques. This presentation is a summary of updates to these techniques in the last thirty years. The Daisy Incubator by ANKOM Technology has been marketed for over twenty-five years. This product resulted in standardization of materials and methods used to measure in vitro true digestibility. The biological component of the technique, ruminal fluid, is still a variable component since it is influenced by fistulated animal diet and collection and transport procedures. Despite several calls through review papers over the last thirty years, the in situ experimental technique is not standardized and there remains variation among laboratories and experiments. Animal species, ingredients and quantity of animal diet, grind size of the test material, bag pore size, ratio of the sample: surface area of bag, replications, sample treatment prior to incubation and after removal, incubation method, microbial contamination, bag washing, and even laboratory balance weigh method contribute to the variation among in situ experiments. Once in situ data is obtained, it is typically fitted to a first order exponential model and parameters estimated without determining if the model is the best fit. Perhaps understanding the reasons that standardization of in situ methodology have failed would facilitate ways to make standardization possible. In the meantime, careful in situ experimental technique results in measures that are valuable inputs into models for nutrient requirements, intake, and digestibility and an increase in knowledge about ruminal degradation kinetics, despite the inability to compare results across laboratories or experiments.